The Influence of Human Development Index (HDI) and Population on Unemployment Rate in Toraja Regency - Palette, Stevanie; Kalangi, Josep Bintang; Masloman, Irawaty (Formosa Journal of Applied Sciences, 2024)
One of the economic issues that can impede healthy economic growth is the unemployment rate, which is typically brought on by a labor force or job seeker population that is out of proportion to the number of open positions. The North Toraja unemployment rate is hard to raise because of this. Community economic development is also difficult. This unemployment rate may make North Toraja residents more exposed to economic and social inequalities if it doesn't drop soon. This study examines how North Toraja Regency's population and HDI effect unemployment. The study employed 2010–2023 Central Bureau of Statistics North Toraja data. Time series were saved. With Eviews 12, data is analyzed using multiple linear regression. The study found that the HDI lowers North Toraja unemployment.